TEKNIK PERANCANGAN PRIMER UNTUK SEKUEN GEN MDR-1 VARIAN 1199 PADA SAMPEL BUFFY COAT PASIEN ANAK DENGAN LLA - Yustinadewi, Putu Desy; Yustiantara, Putu Sanna; Narayani, Inna (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018)DO - 10.24843/metamorfosa.2018.v05.i01.p16, 2018)
Single Nucleotide Polymorphism (SNP) 1199 can be identified using a buffy coat sample by the Polymerase Chain Reaction (PCR) method. The components required in the PCR process are DNA templates; A pair of primers, a short oligonucleotide having a complementary nucleotide sequence with the DNA nucleotide sequence of the template; DNTPs (Deoxynucleotide triphosphates); PCR buffer; Magnesium chloride (MgCl2) and DNA polymerase enzymes (Handoyo and Rudiretna, 2001). Primers greatly affect the specificity and sensitivity of PCR reactions. The design of a primer is one of the determinants of the success of a PCR process (Ebd-Elsalam, 2003). Primer for sequencing MDR-1 variant 1199 gene successfully designed in the best condition. The length of the forward primary sequence of 21 oligonucleotides and reverse amounts of 20 oligonucleotides with a fragment of 225 bp.